Effects of Relaxation Therapy in the Management of Depression in Gestational Diabetes - Javeria Shahzadi, Wardah Ijaz Qazi, Sania Aziz, Mariam Naz, Sidra Hanif, Hanifa Suleman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Gestational diabetes becoming a common gestational complication today generation. Data on effectiveness of relaxation therapy and relation of depression to that was not much significant. The study was design to measure the effectiveness of relaxation therapy in management of depression in GDM mothers. Objective: To determine the effects of relaxation therapy for the management of depression in gestational diabetes. Methodology: Current study is a randomized controlled trial including 40 participants who were randomly selected into control and interventional group. Interventional group was treated with Laura Mitchell Relaxation Techniques and breathing exercises once a week and followed for 6 weeks whereas control group was given conventional pharmacotherapy treatment only. Edinburgh Postnatal. Depression Scale (EPDS) has been used to evaluate the depression in both groups at the baseline and after 6 weeks. Statistical analysis was done by SPSS v.21. Paired t-test and independent t-test has been used to interpret the data. Results: Mean age of mothers was 30.97 ±5.17 years. The mean gestational age of mothers was 33.82±3.26 weeks; control group had mean gestational age (GA) 33.60±2.58 weeks and interventional group had mean G.A 34.05±3.88 weeks. The paired t-test value for both groups showed a significant increment i.e. (p <0.05) in reduction of depression that was measured through EPDS, pre-treatment mean value for group control is 16.75 ± 2.6 and post 6 weeks is 10.40 + 2.3 while pre-treatment mean for interventional group is 15.70 + 1.6 and post is 7.70 + 1.4.The independent t-test when applied on post-treatment results, it showed result with P <0.001 which shown significant reduction of pain in interventional group. Conclusion: Relaxation exercises are significant in reducing depression in females with gestational diabetes. Keywords: Edinburgh Postnatal Depression Scale (EPDS), Gestational Diabetes Mellitus (GDM), Laura Mitchell Relaxation Techniques, Relaxation Therapy.